The aswang realm as perceived by Taclobanons - Lim, Joan Segundina I.; Mate, Sharisse May E. (2003)
One of the principal aspects of Philippine folklore is the belief in aswang. As used in the study, aswang is a generic term for a creature either male or female that possesses the ability to assume the form of an animal, cleave its body into two and fly, devour internal organs, suck the blood and phlegm of the sick, and eat corpses. The primary problem of the study was explore the nature of the aswang. The research was conducted in the city of Tacloban, Leyte. Thirty-one descriptive accounts were gathered from fifteen (15) informants through unstructured interviews. It was found in the study that the aswang is endowed with preternatural qualities and capacities that are beyond the ordinary, such as the ability to assume the animal form. Likewise, humans have learned to identify and detect the presence of the creature. Individuals, who are old and exhibit the rather odd behaviors such as eating raw chicks, are highly suspected as aswangs. The researchers also found that a dying aswang may transmit its power to a member of the family. Another way of acquiring the power of the aswang is through consuming the food prepared by the creature. Finally, findings show that people have adopted various means of protecting themselves against the aswang, such as praying the oracion and the Apostle's Creed. Hence, findings of the study reveal that the Taclobanons have firmly established beliefs about the existence of aswang.